Metode K-Means Clustering Dalam Merancang Strategi Promosi Penerimaan Mahasiswa Baru Pada STIE Serelo Lahat - Mohamad Farozi (UNIVERSITAS INDO GLOBAL MANDIRI, 2022)
New Student Admission at STIE Serelo Lahat is an annual activity carried out by STIE Serelo Lahat. A marketing strategy with several promotions is carried out as an initial activity to get new students. Marketing strategies are always evolving from year to year by analyzing student data from new student registrations to accepted students stated and used as the basis for analyzing targeted and accurate marketing strategies. Cluster formation is one of the techniques used in extracting the trend pattern of a data. K-Means Clustering is able to find and group data that has characteristics (similarities) between one data and other data and different data in different groups will show unstructured data groups becoming structured. This study applies the K-Means Clustering Method in designing a promotion strategy for new student admissions at STIE Serelo Lahat based on new student registration data analyzed by the clustering method using the K-Means algorithm so as to produce K-Means group information into three parts with variable values that different so that information is obtained that most of the choices of students in the Management Study Program originating from the Lahat District in Domination are from Private SMA / MA and from East Kikim District originating from Private Vocational Schools and the most registration is in the Second Wave. Furthermore, designing a marketing promotion strategy for New Student Admissions at STIE Serelo Lahat can be determined by using a minimal K-Means clustering approach. This approach makes it possible to have a great opportunity to increase the number of new students at STIE Serelo Lahat. Keyword : K-Means Clustering, Information, Students Admission